The Musgravian transformation in the two-part tariff and other monopoly models - Yang, Chin Wei; Tang, Meng-Chi (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
In this paper, we prove for the first time that a demand ad valorem tax on commodity price is equivalent to the cost payment tax in the two-part tariff model if such a tax is imposed on both admission charge and user’s fee. The same result is found in the third-degree price discrimination model. However, this property is not preserved in the rate-of-return-regulated monopoly model. It relates to the importance of the choice of tax policies not only in a pure monopoly, but also in two-part tariff, third-degree price discrimination and regulated monopoly models
Argumenta Oeconomica, 2019, Nr 1 (42), s. 109-130
Keywords: Musgravian transformation; two-part tariffs; regulated monopoly model